El sentido de la interioridad en Rosalía de Castro - López Castro, Armando (Estudios Humanísticos. Filología, 1991)
El concepto de interioridad es clave en el arte moderno. Bécquer y Rosalía fundan la poesía moderna en España, al devolver a la palabra su interioridad perdida en un momento de sonoras voces. La palabra de Rosalía es natural porque brota de lo más profundo del alma. Voz de la sombra, espacio o lugar de lo interior. The experience of the inner being is a key one in modern art. Bécquer and Rosalía lay the foundations of modern poetry in Spain by returning to the word its original significance at a time when pomposity in form obscured the sensitivity in meaning. Rosalía's voice is natural because it springs from her inner self, her very soul, her inner being: voice of the shadow, space or place of the inner being.